If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1d = -11 Solving 5 + -1d = -11 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1d = -11 + -5 Combine like terms: 5 + -5 = 0 0 + -1d = -11 + -5 -1d = -11 + -5 Combine like terms: -11 + -5 = -16 -1d = -16 Divide each side by '-1'. d = 16 Simplifying d = 16
| 225=-8x-7(1+3x) | | 23/x=23 | | 5k^2+17k-20=-8 | | 2(c-9)=4 | | 7K=-91 | | 3y-2y=16 | | -x+16=3x+4 | | 5x^4-x=0 | | 3=z-4/2 | | 170-(160-x)+x=180 | | 2[2(6x+3)-5(2x-4)]= | | 3(x-3)-x=5 | | 6x+1=4x-30 | | 7=p*4+8 | | -2(c+18)=-8 | | 5x-23=56 | | X+8+6x=-69 | | -x+23=x+7 | | d/dx(f(3x^2)) | | -6x-12=4(2x-3) | | (x^4)^-1/4 | | 4u=u+48 | | 26-4x=7x-29 | | 84=6(n+8) | | 123/324 | | 84=6(n-8) | | .6x+1.9x= | | x(-3)+5x= | | 6p=p+5 | | Cos=0.7 | | x+82=-11 | | 9x-4=3+2x |